Representations of Policing Problems and Body-Worn Cameras in Existing Research - Backman, Christel (International criminal justice review, 2022)
In this article, we analyze scholarly publications on body-worn cameras (BWCs) to shed light on scholars’ grounding assumptions about BWC technology and the policing problems assumed to be amended by it. We conducted a systematic search and a double-blind review, including 90 peer-reviewed journal articles, and analyzed how scholars warrant their studies, their findings and their recommendations. We found that BWC research largely investigates the effectiveness of BWCs worn by police officers in the United States and build upon a set of dominant policing problem representations: the police crisis in the United States and the police use of force, lack of oversight and control of police officers, citizen dissatisfaction and lack of police legitimacy, and police officer resistance toward BWC use. Assumptions underlying all four problem representations is that BWC technology will amend these problems and is legitimate and useful if the public supports it. Taken together, this enhances the representation of BWC technology as a self-evident means of improving community relations and police legitimacy in the United States. Finally, we provide recommendations for future research on BWCs, particularly the need for research departing from altogether different problem representations.